2012
DOI: 10.1097/ede.0b013e31826767c2
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Air Pollution in a Cohort of Patients With Chronic Obstructive Pulmonary Disease

Abstract: COPD patients are more susceptible to air pollutants, especially PM10 and NO2. These results suggest a need for more protective air pollution standards for susceptible groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 26 publications
3
38
0
2
Order By: Relevance
“…However, these values represent the average effect estimate for a distribution of effects within the study population. Acute inflammatory responses to air pollution resulting in reduced lung function may be part of the triggering mechanism for the reported association between short-term air pollution exposure and respiratory hospitalization and mortality (2)(3)(4). Few studies have examined health outcomes in association with exposure levels defined by the AQI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these values represent the average effect estimate for a distribution of effects within the study population. Acute inflammatory responses to air pollution resulting in reduced lung function may be part of the triggering mechanism for the reported association between short-term air pollution exposure and respiratory hospitalization and mortality (2)(3)(4). Few studies have examined health outcomes in association with exposure levels defined by the AQI.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence has shown that modest shortterm increases in ambient air pollution, especially PM 2.5 (particles with an aerodynamic diameter < 2.5 mm) and ground level ozone (O 3 ), but also nitrogen dioxide (NO 2 ), increase risk of hospitalization for chronic obstructive pulmonary disease (COPD) and respiratory mortality (1)(2)(3)(4). Several studies have found that short-term (1-3 d) increases in PM 2.5 , NO 2 , and O 3 are associated with decreases in FEV 1 , FVC, and/or peak expiratory flow rate in healthy subjects (5)(6)(7)(8)(9)(10)(11) and in those with preexisting COPD or asthma (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In contrast, the large American multicity study, NMMAPS, did not find such associations between NO 2 and daily mortality: only a small and non-significant association of NO 2 with all-cause mortality was reported after adjustment in a two-pollutant model with PM 10 ; no association was found in a multipollutant model, which included PM 10 , carbon monoxide, SO 2 and ozone (Zeka & Schwartz, 2004;see Table 6). Previous NMMAPS analyses of a subset of the 90 cities in the United States in this study found approximately a 0.7% (95% CI: 0.3-1.2%) 6 increase in all-cause mortality per 4 Chiusolo et al (2011), Chen et al (2012a, Faustini et al (2012) and Chen et al, 2013 were published after the last update of APED in April 2011 and are not presented in Table 5. Two further papers (Koop & Tole (2004) and Roberts & Martin(2005)), which explored approaches to estimating the health effects of multiple air pollutants, are also available and are included in the information presented in Table 5.…”
Section: Mortalitymentioning
confidence: 96%
“…Twenty-four time-series studies of mortality, which used two-pollutant and/or multipollutant models for NO 2 , have been published since the 2005 global update of the WHO air quality guidelines (Burnett et al, 2004;Dales et al, 2004;Kan, Jia & Chen, 2004a,b;Zeka & Schwartz, 2004;Simpson et al, 2005a;Díaz, Linares & Tobías, 2006;Samoli et al, 2006;Brook et al, 2007;Qian et al, 2007Qian et al, , 2010Yamazaki et al, 2007;Chen et al, 2008;Hu et al, 2008;Ren Y et al, 2008c;Wong et al, 2008;Breitner et al, 2009;Chen et al, 2010a;López-Villarrubia et al, 2010;Park, Hong & Kim, 2011;Chiusolo et al, 2011;Chen et al, 2012a,b;Faustini et al, 2012;Chen et al, 2013). 4 All of these papers included adjustments for a metric of PM; 17 of the 24 papers reported positive, though not always statistically significant, short-term associations of NO 2 with mortality for a range of diagnoses and age groups, after adjustment for a PM metric.…”
Section: Mortalitymentioning
confidence: 99%
“…라 심혈관계 사망률 또는 입원율도 증가시키며 (Atkinson et al, 2013), 어린이나 천식 환자, 고령 자 등과 같이 상대적으로 취약한 환자들에게 더 큰 영향을 미친다는 결과도 발표되었다 (Faustini et al, 2012). 입자상 물질의 건강 영향은 기후 또는 기상 변 화의 영향을 받는 것으로 알려져 있으며 (Díaz et al, 2012) …”
Section: 입자상 물질은 급성 및 호흡기계 사망률뿐만 아니unclassified